Social Media as Effective Tool for Understanding Customer Experience: A Systematized Review - Adisu Fanta , Bate; Ayman, Balawi (Marketing & Menedzsment, 2022)
THE AIMS OF THE PAPER Social media play an indispensable role in utilizing, building, and promoting companies' brands and communicating customer's experience in the current digital age. However, literature has not sufficiently addressed how social media could be utilized to understand customer experience. This paper, hence, aims to describe the roles and importance of social media in knowing about customers experience and offers tips for companies on how to select, target, and deliver the right content for the social media platforms at all touch points along their purchasing journey. METHODOLOGY The systematized review (SR) method was followed to trace out & analyze the data. The EBSCO discovery of science was utilized to search for articles. Among the databases in it, emphasis was given to academic search complete, business source premium & science direct. Out of the total (289) search query results, over forty-five articles were synthesized after imposing limiters, removing duplicates, and imposing none-business settings. MOST IMPORTANT RESULTS Social media is a multi-purpose tool that offers services ranging from brand awareness creation, advertisement, product sales information, to soliciting post-purchase customers' experience and then catalyzes two-way communication between marketers and users. Its effectiveness depends not only on selecting social media and posting at the right time but also on designing the right content based on the nature of a product: hedonic or functional. The social media content of hedonic products, consumed for enjoyment and luxury purposes, has more customer reactions than functional products consumed as common goods. Besides, as customers rely more on other customers' reviews, user-generated content is more valuable than firm-generated content, especially for hedonic products. Thus, the content-product-media match must find its proper place. Additionally, the authors elaborated on the relationship between 4 touching points (brand-owned, partner-owned, customer-owned, social/independent, based on (Verhoef and Lemon 2016) and 3 stages of the purchase process (pre-purchase, during purchase, post-purchase). RECOMMENDATIONS Customer experience analysis should include all affective, physical, cognitive, sensorial, emotional, and social responses of customers towards brands. A company also needs to identify and, thoroughly, keep tracing customers' reactions at all touchpoints in all purchase journey phases using tools like 'SentiStrength' and 'Weka software'. It should be a top priority for management. They should place a responsible person or team to utilize social media and collect data on customer's experience in a separate IT-supported office.